2016
DOI: 10.1038/srep37061
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-mediated changes in conformational dynamics of NpmA: implications for ribosomal interactions

Abstract: Aminoglycosides are broad-spectrum antibiotics that bind to the 30S ribosomal subunit (30S) of bacteria and disrupt protein translation. NpmA, a structurally well-characterized methyltransferase identified in an E. coli clinical isolate, catalyzes methylation of 30S at A1408 of the 16S rRNA and confers aminoglycoside resistance. Using sucrose cushion centrifugation and isothermal titration calorimetry, we first confirmed the binding between NpmA and 30S. Next, we performed amide Hydrogen/Deuterium Exchange Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Alterations in conformational dynamics upon ligand binding were described in several earlier reports [11,12,14,17,19,[21][22][23]25,126,130]; in selected studies, an allosteric effect could also be identified. A great example of perturbed conformational dynamics was published by Zhou et al in 2017 [25], where HDX-MS analysis shed light on the role of conformational dynamics, which was considerably altered upon ligand binding, in the mechanism of action of the DXPS enzyme; the closed conformation of DXPS proved to be critical for stabilization of the transition state, whereas the open conformation is apparently required for releasing the lactyl-thiamin diphosphate final product.…”
Section: Analysis Of Protein Interactionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Alterations in conformational dynamics upon ligand binding were described in several earlier reports [11,12,14,17,19,[21][22][23]25,126,130]; in selected studies, an allosteric effect could also be identified. A great example of perturbed conformational dynamics was published by Zhou et al in 2017 [25], where HDX-MS analysis shed light on the role of conformational dynamics, which was considerably altered upon ligand binding, in the mechanism of action of the DXPS enzyme; the closed conformation of DXPS proved to be critical for stabilization of the transition state, whereas the open conformation is apparently required for releasing the lactyl-thiamin diphosphate final product.…”
Section: Analysis Of Protein Interactionsmentioning
confidence: 90%
“…Last year, a group of eminent researchers in the field formulated clear recommendations for performing and interpreting HDX-MS experiments [ 4 ] and hence paved the way towards truly standardized experiments. The applications of HDX-MS are very versatile: they include studies of protein complexes [ 5 , 6 , 7 , 8 , 9 , 10 ], ligand binding [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], dynamic properties like conformational changes and folding/unfolding/refolding [ 26 ], conformational changes that arise from allosteric effects [ 27 , 28 , 29 ], structure and stability of biopharmaceuticals [ 17 , 30 , 31 ] and epitopes [ 15 , 32 , 33 ], etc. Unlike several other biophysical techniques, HDX-MS possesses the advantages of no or very high size limit [ 8 ] and is useful for studying individual proteins as well as large complexes [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…While gross structural changes in the ␤5/6 linker deletion variant are unlikely given its retained ability to bind 30S, loss of the ␤5/6 linker could have long-range impacts on NpmA structure or conformational dynamics, which in turn impact SAM/SAH affinity. Recent hydrogen-deuterium exchange analysis of NpmA-SAM/SAH complexes suggests the potential for allosteric communication between the ␤2/3 linker 30S binding surface, the ␤5/6 linker, and the cosubstrate binding pocket between them (25). NpmA interaction with cosubstrate was also previously speculated to be influenced by 30S substrate binding (20,22), based in part on the observation that substitution of ␤6/7 linker residue S195 decreases SAM/SAH affinity by Ͼ50-fold, yet the variant enzyme is still capable of conferring wild-type-level resistance.…”
Section: Discussionmentioning
confidence: 99%